2013
DOI: 10.1136/bjophthalmol-2012-302391
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-masked trial comparing the visual outcome after treatment with ranibizumab or bevacizumab in patients with neovascular age-related macular degeneration

Abstract: Bevacizumab was equivalent to ranibizumab for visual acuity at all time points over 1 year. There was no significant difference of decrease of retinal thickness or number of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(132 citation statements)
references
References 24 publications
6
118
1
7
Order By: Relevance
“…Table 3 compares findings from this study with clinical trial results. The CATT 6 and IVAN 7,9 studies achieved mean improvement from 0 to 12 months of 6.8 and 5.0 letters, respectively, with seven injections, whereas the Groupe d'Etude Français Avastin versus Lucentis dans la DMLA néovasculaire (GEFAL) 17 and Multicentre Anti-VEGF Trial in Austria (MANTA) 18 studies showed mean improvement of 2.9 and 4.1 letters, respectively, with six injections, which is comparable to the mean improvement of 2.5 letters with six injections in this study. These results suggest that a similar benchmark of +2.5 letters improvement (0-12 months) with six injections represents quality ongoing care that is achievable in a real-world, public hospital setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 compares findings from this study with clinical trial results. The CATT 6 and IVAN 7,9 studies achieved mean improvement from 0 to 12 months of 6.8 and 5.0 letters, respectively, with seven injections, whereas the Groupe d'Etude Français Avastin versus Lucentis dans la DMLA néovasculaire (GEFAL) 17 and Multicentre Anti-VEGF Trial in Austria (MANTA) 18 studies showed mean improvement of 2.9 and 4.1 letters, respectively, with six injections, which is comparable to the mean improvement of 2.5 letters with six injections in this study. These results suggest that a similar benchmark of +2.5 letters improvement (0-12 months) with six injections represents quality ongoing care that is achievable in a real-world, public hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…The CATT 6 and GEFAL 17 considered a difference of five EDTRS letters to represent noninferiority, whereas the MANTA 18 considered a difference of seven letters to be noninferior. 18 Because of the 'ceiling effect', whereby eyes starting treatment with good VA have little room for further improvement, many measures are dependent on the starting VA. 11,12,20 Adjusting for age, starting VA, number of injections, and visits reduced, but did not eliminate the significant variation between centres, suggesting there are other unmeasured factors that contribute to these variations in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the relative efficacies of these bevacizumab and ranibizumab for treatment of AMD and found no difference in visual acuity or complications (Subramanian et al 2010;Biswas et al 2011;Chakravarthy et al 2013;Kodjikian et al 2013;Krebs et al 2013). The CATT study found monthly treatments of bevacizumab not inferior to monthly ranibizumab, although ranibizumab had a greater mean decrease in central retinal thickness and bevacizumab had more serious systemic adverse events (CATT Research Group et al 2011).…”
Section: Rvomentioning
confidence: 99%
“…Meta-analyses Figure 30 shows meta-analyses of safety outcomes from the CATT, GEFAL, IVAN, LUCAS (presented at the 2013 meeting of the American Association for Ophthalmology), MANTA and Subramanian et al trials comparing ranibizumab and bevacizumab 22,[42][43][44] (available information for the BRAMD trial reported only by MedDRA System Organ Class and did not distinguish deaths from other SAEs). The CATT 22 and IVAN trials followed participants for 2 years, and the other four trials reported data to 1 year after recruitment.…”
Section: Non-serious Adverse Eventsmentioning
confidence: 99%
“…However, interactions that were both non-significant and smaller than both main effects were excluded from the analysis to avoid loss of statistical power. Lack of statistical significance was not considered sufficient grounds to ignore interactions, as ignoring genuine interactions introduces bias 43,85 and can give misleading conclusions. 130 We evaluated different methods for identifying important interactions on simulated trial data, which demonstrated that including interactions that are larger than main effects outperformed using statistical significance or Bayesian/ Akaike information criteria for identifying influential interactions.…”
mentioning
confidence: 99%